Hematopoietic Cell Transplantation in Patients With Primary Immune Regulatory Disorders (PIRD): A Primary Immune Deficiency Treatment Consortium (PIDTC) Survey - Chan, Alice Y.; Leiding, Jennifer W.; Liu, Xuerong; Logan, Brent R.; Burroughs, Lauri M.; Allenspach, Eric J.; Skoda-Smith, Suzanne; Uzel, Gulbu; Notarangelo, Luigi D.; Slatter, Mary; Gennery, Andrew R.; Smith, Angela R.; et al. (Frontiers in Immunology, 2020)
Primary Immune Regulatory Disorders (PIRD) are an expanding group of diseases caused by gene defects in several different immune pathways, such as regulatory T cell function. Patients with PIRD develop clinical manifestations associated with diminished and exaggerated immune responses. Management of these patients is complicated; oftentimes immunosuppressive therapies are insufficient, and patients may require hematopoietic cell transplant (HCT) for treatment. Analysis of HCT data in PIRD patients have previously focused on a single gene defect. This study surveyed transplanted patients with a phenotypic clinical picture consistent with PIRD treated in 33 Primary Immune Deficiency Treatment Consortium centers and European centers. Our data showed that PIRD patients often had immunodeficient and autoimmune features affecting multiple organ systems. Transplantation resulted in resolution of disease manifestations in more than half of the patients with an overall 5-year survival of 67%. This study, the first to encompass disorders across the PIRD spectrum, highlights the need for further research in PIRD management.